EFEKTIVITAS PENDEKATAN CONTEXT TEACHING LEARNING (CTL) TERHADAP KETERAMPILAN MENULIS BAHASA JERMAN TINGKAT A2 MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JERMAN - Soumokil, Piet; Lestuny, Carolina; Kinanti, Theresya (Universitas Pattimura, 2025)
Writing is one of the productive skills in foreign language learning that requires systematic thinking, vocabulary mastery, and a good understanding of grammar. At A2 level, students are expected to be able to convey simple ideas in writing with the correct structure and appropriate context. The Contextual Teaching and Learning (CTL) approach is one of the learning strategies that links the subject matter with students' real experiences, so it is expected to increase their motivation and writing ability. This study aims to determine the effectiveness of the CTL approach on German writing skills of A2 level students. The research was conducted using experimental method in German Language Education Study Program. The research subjects were students who took the A2 level writing skills course. The data collection instrument was a writing test that was prepared based on the indicators of A2 level writing skills according to the Goethe Institute. The results of the analysis showed that students who took part in learning with the CTL approach experienced a significant improvement in writing skills. This is evidenced by the results of statistical tests which show that t-count value of -13.330 with a significance (p-value) of 0.000 was obtained. Due to the significance value <0.05, the null hypothesis is rejected. That is, there is a significant difference between the pre-test and post-test scores. This shows that the CLIL approach has a significant effect on improving students' German speaking skills. Based on these findings, the CTL approach is considered effective in supporting the development of German writing skills, especially at the A2 level. Therefore, this approach can be a viable alternative to be applied in the learning process to create a more meaningful and contextualized learning experience for students.